Trends and risk factors in tribal vs nontribal preterm deliveries in Gujarat, IndiaAJOG Global Reports at a Glance - Shital Shah, MPA; Shrey Desai, MD, MPH; Tushar Desai, BAMS; Daria Szkwarko, DO, MPH; Gayatri Desai, MD (Elsevier, 2021)
BACKGROUND: Although risk factors of preterm deliveries across the world have been extensively studied, the trends and risk factors of preterm deliveries for the population of rural India, and specifically tribal women, remain unexplored. OBJECTIVE: The aim of this study was to assess and compare the preterm delivery rates among women from a rural area in Gujarat, India, based on socioeconomic and clinical factors. The second aim of the study was to assess and identify predictors or risk factors for preterm deliveries. STUDY DESIGN: This was a retrospective medical record review study investigating deliveries that took place at the Kasturba Maternity Hospital in Jhagadia, Gujarat, from January 2012 to June 2019 (N=32,557). We performed odds ratio and adjusted odds ratio analyses of preterm delivery risk factors. Lastly, we also considered the neonatal outcomes of preterm deliveries, both overall and comparing tribal and nontribal mothers. RESULTS: For the study period, the tribal preterm delivery rate was 19.7% and the nontribal preterm delivery rate was 13.9%; the rate remained consistent for both groups over the 7-year study period. Adjusted odds ratios indicated that tribal status (adjusted odds ratio, 1.16; 95% confidence interval, 1.08-1.24), maternal illiteracy ((adjusted odds ratio, 1.29, 95% confidence interval, 1.18-1.42), paternal illiteracy (adjusted odds ratio, 1.27; 95% confidence interval, 1.15-1.410), hemoglobin <10 g/dL (adjusted odds ratio, 1.41; 95% confidence interval, 1.32-1.51), and a lack of antenatal care (adjusted odds ratio, 2.15; 95% confidence interval, 1.94-2.37) are significantly associated with higher odds of preterm delivery. The overall stillbirth rate among tribal women was 3.06% and 1.73% among nontribal women; among preterm deliveries, tribal women have a higher proportion of stillbirth outcomes (11.77%) than nontribal women (8.86%). CONCLUSION: Consistent with existing literature, risk factors for preterm deliveries in rural India include clinical factors such as a lack of antenatal care and low hemoglobin. In addition, sociodemographic factors, such as tribal status, are independently associated with higher odds of delivering preterm. The higher rates of preterm deliveries among tribal women need to be studied further to detail the underlying reasons of how it can influence a woman's delivery outcome.